Readdressing the Trade Effect of the Euro: Allowing for Currency Misalignment - Jan Hogrefe; Benjamin Jung; Wilhelm K. Kohler (Verein für Socialpolitik, 2010)
We know that euro-area member countries have absorbed asymmetric shocks in ways that are inconsistent with a common nominal anchor. Based on a reformulation of the gravity model that allows for such bilateral currency misalignment, we disentangle the conventional trade cost channel and trade effects deriving from currency misalignment. Econometric estimation reveals that the currency misalignment channel exerts a significant trade effect on bilateral exports. We retrieve country specific estimates of the euro effect on trade based on misalignment. This reveals asymmetric trade gains and heterogeneous outlooks across countries for the costs and benefits from adopting the euro.
Keywords: F12; F13; F15; 330; gravity model; euro effect; European divergence